Jobs for Youth/Des emplois pour les jeunes: Denmark 2010 - Reeves, Marian (My University, 2010)
Improving the performance of youth on the labour market is a crucial challenge in OECD countries facing persistent youth unemployment. As labour markets become more and more selective, a lack of relevant skills brings a higher risk of unemployment. Whatever the level of qualification, first experiences on the labour market have a profound influence on later working life. Getting off to a good start facilitates integration and lays the foundation for a good career, while a failure can be difficult to make up. Ensuring a good start will require co-coordinated policies to bring the education system closer to the labour market, to help disadvantaged young people to find a job or participate in a training course and to facilitate the hiring of young people by firms. OECD has launched a series of reports on the school-to-work transition process in 16 countries, including Denmark. Each report contains a survey of the main barriers to employment for young people and an assessment of the adequacy and effectiveness of existing measures to improve the transition from school-to-work, and a set of policy recommendations for further action by the public authorities and social partners. This report is based on the proceedings of a seminar and is published in English. Read the Summary also available in French.
Keywords: Adolescents and youth; Labour market; Learning, education and training